Multiculturalism and Human Rights: Navigating the Tension Between Cultural Relativism and Universal Norms Among Indonesian University Students - Faika Burhan; Abdul Jalil; Faza Achsan Baihaqi; Rayhan Hadiansah (Yayasan Cipta Anak Bangsa (YCAB) Publisher, 2026)
Background: The relationship between multiculturalism and human rights (HAM) represents one of the most persistent and productive tensions in contemporary political philosophy, legal theory, and social science. Since the adoption of the Universal Declaration of Human Rights (UDHR) in 1948, scholars and practitioners have grappled with a fundamental question: can a universalist framework of rights coexist with the deep diversity of cultural, religious, and customary systems that characterize human societies Objectives: This study examines the perceptions and attitudes of Indonesian university students toward the tension between cultural relativism and universal human rights norms within a multicultural society. Method: Drawing on in-depth interviews with twelve informants from diverse academic disciplines at Universitas Halu Oleo, this qualitative research explores how young Indonesians conceptualize human rights in relation to cultural identity, gender equality, religious freedom, and state governance. Result: Findings reveal that participants generally affirm the universality of core human rights principles while simultaneously acknowledging the contextual importance of local cultural values. Tensions most frequently arise in three domains: women's rights and gender-based customary practices, the accommodation of minority religious identities in majority-dominated spaces, and the relationship between customary law (hukum adat) and national legal frameworks. Conclusion: The study contributes to ongoing scholarly debates on multicultural human rights education and highlights the need for dialogic approaches that bridge international norms with culturally embedded value systems in the Indonesian context. Implications for curriculum development and intercultural policy are discussed. Keywords: multiculturalism, human rights, cultural relativism, university students, religious freedom